56. PHARMACISTS' KNOWLEDGE, ATTITUDES AND CHALLENGES TOWARDS COUNTERFEIT MEDICINE IN HO CHI MINH CITY: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2025)
Background: Dengue Fever (DF) is one of the infectious diseases in Vietnam, spreading rapidly and causing severe impacts on health, lives, and economic burdens on society. Disease prevention and control pose a significant challenge for the healthcare sector.Objective: To assess the knowledge, attitudes, and practices (KAP) regarding dengue fever prevention among students at Lac Hong University in 2024.Method: A descriptive cross-sectional study using a convenience sampling method, conducted through direct interviews with pharmacy students based on a structured questionnaire. The study was carried out from October 2024 to November 2024. The Chi-square test, with a significance level of p ≤ 0.05, was used to determine participants' general characteristics that affect their knowledge, attitude, and practice.Results: Among the 491 students who participated in the study, good knowledge, attitudes, and practices were observed in 74.1%, 60.5%, and 52.5% of participants, respectively. Social media and the internet were the primary sources of information for students (90.6%). Although students demonstrated good knowledge of the disease, misconceptions remained regarding the activity period of Aedes mosquitoes. Most participants had a positive attitude, but some lacked confidence in the disease recovery process and believed that the public was not well-informed about prevention measures. Preventive actions mainly focused on waste cleanup and the use of mosquito repellent. Cohabitation status has a significant influence on students' knowledge of the disease.Conclusion: There is a need to improve knowledge, attitudes, and practices related to DF through enhanced public education, awareness campaigns, and knowledge dissemination efforts.
Keywords: Knowledge; attitudes; practices; university students; Dengue fever; Vietnam.